Karakteristik Kekuatan Tarik Pada Komposit Hybrid, Serat Rami, Fiberglass, Dan Resin Polyester - Sarudin, Sarudin; Sudarsono, Sudarsono; Gunawan, Yuspian (Teknik Mesin Universitas Halu Oleo, 2019)
The purpose of this research is to know and analyze the characteristics of tensile strength on hybrid composite, fiberglass, flax fiber, and polyester resin. In this research, the manufacturing of composites uses hand lay-up method. Manufacture of specimens in accordance with ASTM standard D638 – 02 and for tensile testing using standard ASTM D790-02. The method used in data analysis is graph data analysis to see the relationship between interconnected parameters and dependence, which is the size of the specimen 13 mm and the number of variations in the composition of specimen mixture. The results showed that the composition of the mixture that has the highest tensile voltage is in the fraction with the composition of resin mixing 50%, fiberglass 30%, and hemp fiber 20% in three (3) specimen with a value of 36,687 N/mm2, while the Has a value with the lowest chart found in the composition with a resin mixing 50%, and hemp fiber 50%, namely in the two (2) specimen with a value of 21,819 N/mm2. Keyword: Composite hybrid, hemp fiber, fiberglass, polyester resin.